THE IMPACT OF MULTIPLE BLOCKHOLDERS IDENTITY ON EXPROPRIATION OF MINORITY SHAREHOLDERS: Evidence from Indonesia - Edy Kurniawan Bayu Aji (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2016)
This paper explores the impact of multiple blockholders identity on the relation between family firms, excess control rights over cash flow rights, and expropriation of minority shareholders, in the specific case of Indonesia by using a panel of Indonesia companies over the period 2006-2008. Three research questions are investigated: 1. What is the impact of family firms on expropriation of minority shareholders; 2. What is the impact of excess control rights over cash flow rights on expropriation of minority shareholders; 3. To what extent does multiple blockholders identity moderate the relationship between family firms, excess control rights over cash flow rights, and expropriation of minority shareholders.In the theory review, agency theory and stewardship theory are introduced as theoretical foundation, followed by the discussion of corporate governance in Indonesia context. While agency theory specifies the agency problems namely principal-agent conflicts and principal-principal conflicts; stewardship theory discusses that managers are considered as good stewards who will act in the best interest of the owners which ideal for explaining governance in the family business context.In regards to the methodology, ten testable hypotheses are generated for empirical analysis. Multiple regression analysis of panel data applies Ordinary Least Square (OLS) regression to test the impact of multiple blockholders identity on the relation between family firms, excess control rights over cash flow rights, and expropriation of minority shareholders. Finally, the research questions are answered: there is positive correlation between family firms and expropriation of minority shareholders; excess control rights over cash flow rights has positive impact on expropriation of minority shareholders; and multiple blockholders identity namely another family as the second largest blockholders as well as institutional investor generate disparate significant impact on expropriation of minority shareholders. The existence of another family as the second largest blockholders creates expropriation more severe for minority shareholders while the presence of institutional investor is notable to lessen the positive impact of family firms and excess control rights over cash flow rights on expropriation of minority shareholders.